Performance of electrophysiology procedures at an academic medical center amidst the 2020 coronavirus (COVID‐19) pandemic. (20th April 2020) - Rubin, Geoffrey A.; Biviano, Angelo; Dizon, Jose; Yarmohammadi, Hirad; Ehlert, Frederick; Saluja, Deepak; Rubin, David A.; Morrow, John P.; Waase, Marc; Berman, Jeremy; Kushnir, Alexander; Abrams, Mark P.; et al.
Abstract: A global coronavirus (COVID‐19) pandemic occurred at the start of 2020 and is already responsible for more than 74 000 deaths worldwide, just over 100 years after the influenza pandemic of 1918. At the center of the crisis is the highly infectious and deadly SARS‐CoV‐2, which has altered everything from individual daily lives to the global economy and our collective consciousness. Aside from the pulmonary manifestations of disease, there are likely to be several electrophysiologic (EP) sequelae of COVID‐19 infection and its treatment, due to consequences of myocarditis and the use of QT‐prolonging drugs. Most crucially, the surge in COVID‐19 positive patients that have already overwhelmed the New York City hospital system requires conservation of hospital resources including personal protective equipment (PPE), reassignment of personnel, and reorganization of institutions, including the EP laboratory. In this proposal, we detail the specific protocol changes that our EP department has adopted during the COVID‐19 pandemic, including performance of only urgent/emergent procedures, after hours/7‐day per week laboratory operation, single attending‐only cases to preserve PPE, appropriate use of PPE, telemedicine and video chat follow‐up appointments, and daily conferences to collectively manage the clinical and ethical dilemmas to come. We discuss also discuss how we perform EP procedures on presumed COVID positive and COVID tested positive patients to highlight issues that others in the EP community may soon face in their own institution as the virus continues to spread nationally and internationally.